Material particulado atmosférico na cidade de São Carlos- SP: quantificação e identificação de fontes - Bruno, Ricardo Luiz (2005)
In the present work, breathable particulate matter (PM10) concentration was measured in their fine (PM2.5-10) and ultra-fine (MP2.5) fractions, in the municipal district of São Carlos. The samplings were carried out from 2001 to 2004 for PM10 (complemented with data from 1997 to 2001 taken from the research group databank) and for the period of 1 year (2001-2002) for PM2.5. PM10 was sampled with a high volumes sampler, while PM2.5 and PM2.5-10 were sampled with a dichotomous sampler. In order rationalize the seasonal variation MP, the year was separated in two different periods, the so-called dry period characterized by colder months and smaller incidence of rains and the rainy period, characterized by hotter months and by larger incidence of rains. After the collection, XRF analysis were carried out to quantify the chemical elements with mass molar superior to 12 a.m.u.. Also, DIC/DOC (dissolved organic and inorganic carbon) analysis were performed. The results showed 14 chemical elements, on average, both in fne and ultrafine fractions. The chemical elements that appear in larger concentrations in the PM are organic carbon, inorganic carbon, Al, Si, Ca, Ti, K, S and Fe. Two receptor models, the principal factors analysis (PFA) and chemical mass balance (CMB) were used to quantify the probable pollution sources for responsible for the sampled PM in the receptor site. PFA suggests that 3 main sources are responsible for the PM in the ultrafine fraction, both in the dry as well as in the rainy season. As for the fine fraction, the PFA suggests that 4 main sources are responsible for the pollution in the receptor site. The CMB analysis indicates that, for the ultrafine fraction the main source is the gas/particle conversion from sulfur, both in the dry and rainy periods. For the dry period, the biomass burning becomes significant as a pollution source. In the fine fraction of MP, the main sources identified were soil resuspension and vehicular emission.